Internalization of international environmental treaties in Vietnam - Vang-Phu Tran; Thanh Giao Nguyen (Department of Government Studies, Universitas Muhammadiyah Makassar, 2026)
Global integration and the expansion of new-generation free trade agreements have intensified pressure on transitional economies to harmonize domestic legislation with international environmental law. This study examines how Vietnam’s 2020–2025 legislative reforms internalize core obligations derived from the Paris Agreement, Montreal Protocol, Basel Convention, and UNCLOS. Using a functional comparative law approach, it evaluates substantive compatibility, understood as the alignment between domestic statutory provisions, treaty obligations, and operational enforcement mechanisms. The novelty of this research lies in integrating legal transplantation theory with empirical policy analysis to assess not only formal legal convergence but also the institutional capacity required for effective compliance. The findings show that Vietnam has shifted from passive treaty ratification toward proactive regulatory integration, particularly through carbon pricing and Extended Producer Responsibility. However, the study also identifies patterns of isomorphic mimicry, whereby global legal forms are adopted without sufficient implementation capacity, resulting in persistent de facto enforcement gaps. Inter-sectoral tensions, especially between development-oriented land governance and biodiversity protection, further weaken regulatory coherence. This research contributes a conceptual evaluation model for environmental governance and offers practical insights for Global South transitional economies facing similar harmonization challenges.